DEVELOPING COMMUNICATIVE COMPETENCE THROUGH LANGUAGE SKILLS IN AN ESP COURSE - A CASE OF TECHNICAL ENGLISH - Marina Oštarić; Nataša Perinčić Tičić (Elektronički Zbornik Radova Veleučilišta u Šibeniku, 2022)
This article investigates the importance of developing communicative competence through language skills in English for Specific Purposes (ESP) offered as a Technical English course in tertiary education. As Technical English courses are predominantly designed to prepare students for the future professional environments in the modern world, competent communication in English is to be mastered. For this reason, the integration of language skills in a Technical English course is imperative in teaching practices with students within a range of technical fields.